Sinkronisasi Pelaksanaan Pemilihan Umum Serentak terhadap Perencanaan Pembangunan Nasional 2025 – 2045 - Dirkareshza, Rianda; Sadiawati, Diani; Setiadi, Wicipto (Fakultas Hukum Universitas Udayana, 2024)
In th Simultaneous elections are considered to have a bad tendency by a number of people, also considered not to see a big future impact on national development planning in 2025 – 2045. The purpose of this article is to present a new perspective on seeing simultaneous elections by linking national development planning as a future impact on people's welfare. This research is qualitative by using a statue approach in comparing the laws and regulations that change in each period of simultaneous elections and the synchronization of laws and regulations with national development planning. The conseptual approach is used as the basis for the author to conceptualize the synchronization of simultaneous elections to national development planning in the 2025 - 2045 RPJPN. The results of the research from this article show three outlines: First, the impact of holding simultaneous elections results in harmony in the implementation of national development planning. Second, the synchronization of simultaneous elections to national development planning eliminates the disparities between regions that occur in Indonesia. Third, the results of synchronization as discussed will result in a phased walfare state in 2025 - 2045.